CULTURALLY RESPONSIVE TEACHING IN FOREIGN LANGUAGE CLASSROOM: ENHANCING ENGAGEMENT AND INTERCULTURAL COMPETENCE - Turgunova Rano (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
This article investigates the importance of Culturally Responsive Teaching (CRT) in foreign language schools. It contends that incorporating students’ cultural backgrounds and various experiences is critical to encouraging true involvement, improving linguistic learning, and creating genuine intercultural communicative competence. The essay examines current literature to demonstrate the significance of cultural context in language learning. It then offers and analyses practical, evidence-based techniques for FL instructors to include culturally relevant features into their teaching. The debate is on how CRT may help FL classrooms become more inclusive, equitable, and effective learning environments, preparing students for meaningful engagement in a globalized society. Implementation challenges, the growing role of the FL educator, recommendations for future study, and teacher professional development are all taken into consideration.